LATAR BELAKANG PEMILIHAN LOKASI PADANG LAWAS SEBAGAI SITUS PERCANDIAN - Sukawati Susetyo (Naditira Widya, 2009)
Padang Lawas is a temple complex of 1.500 km square meter in width and consists of at least 20 biaro. Most of the temples lie in jurisdiction of Kabupaten Tapanuli Selatan and others are in Kabupaten Mandailing Natal, North Sumatra. The general structures of Padang Lawas temples are of bricks, however, other components are sandstone. Sandstone is commonly found in Gunung Tua, which is assumed to be the resource of temple materials. Besides its proximity to raw materials, the site was chosen due to its geographical position close to Barumun and Pane River; such position accelerated communicaton with the outside world, for instance Barus, a well-known international port. This article discusses whether natural resources played significant role in choosing a prospective temple or settlement site.